2021
DOI: 10.7759/cureus.13929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monthly and Bi-Monthly 50,000 International Units (IU) Maintenance Therapy With Vitamin D3 on Serum Level of 25-Hydroxyvitamin D in Adults: A Randomized Controlled Trial

Abstract: Background Vitamin D deficiency is a prevalent condition worldwide. Identification of optimal supplementation approaches for maintaining normal vitamin D level in healthy adults is still required. It has been clearly established that sun exposure and diet do not provide the recommended daily amount of vitamin D, and that vitamin D supplementation is needed to maintain normal levels in the Saudi population. The aim of this study was to compare the efficacy of two regimens, monthly and bimonthly doses of 50,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…In several studies the effect of different durations of supplementation with 50,000 IU Vit. D has been investigated on different health outcomes [ 20 23 , 28 ]. In a study by Penckofer et al has shown that supplementation with 50,000 IU weekly for 6 months increased the serum Vit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies the effect of different durations of supplementation with 50,000 IU Vit. D has been investigated on different health outcomes [ 20 23 , 28 ]. In a study by Penckofer et al has shown that supplementation with 50,000 IU weekly for 6 months increased the serum Vit.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies the effect of different durations of supplementation with 50,000 IU Vit. D has been studied with different health outcomes [ 20 23 ]. However determining the Vit.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, research has indicated that the swift dissemination of COVID-19 within Saudi Arabia (KSA) has been associated with an upsurge in psychological symptoms among various segments of the population. These symptoms encompass stress, affective symptoms, insomnia, and obsessive-compulsive symptoms (33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the majority of the conducted studies in Saudi Arabia have taken place during the pandemic and lockdown periods, providing valuable insights into various aspects of the situation (33,34,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%
“…Схемы лечения дефицита и недостаточности витамина D. Коррекция дефицита витамина D (уровень 25(OH)D менее 20 нг/мл)  50 000 МЕ еженедельно в течение 8 недель внутрь  200 000 МЕ ежемесячно в течение 2 месяцев внутрь  150 000 МЕ ежемесячно в течение 3 месяцев внутрь  6000 -8000 МЕ в день -8 Продолжительность поддерживающей терапии и эффективная поддерживающая терапия для взрослых с целевым достигнутым или исходным уровнем витамина D четко не определены. Прием 50 000 МЕ витамина D каждые 2 недели (что эквивалентно 3500 МЕ в сутки) показал эффективность в поддержании уровня 25(OH)D в целевом диапазоне выше 30 нг/мл и отсутствие значимых побочных эффектов при наблюдении до 6 лет[90,91]. Суточной дозы в 2000 МЕ, по данным ряда исследований, может оказаться недостаточно для достижения таких показателей[92,93], но в некоторых исследованиях оказались эффективными и более низкие дозы (900 -1800 МЕ в сутки)[94], что подтверждается опытом отечественных экспертов.…”
unclassified